2011
DOI: 10.1002/jbmr.196
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and bioavailability of stabilized amorphous calcium carbonate

Abstract: Since its role in the prevention of osteoporosis in humans was proven some 30 years ago, calcium bioavailability has been the subject of numerous scientific studies. Recent technology allowing the production of a stable amorphous calcium carbonate (ACC) now enables a bioavailability analysis of this unique form of calcium. This study thus compares the solubility and fractional absorption of ACC, ACC with chitosan (ACC-C), and crystalline calcium carbonate (CCC). Solubility was evaluated by dissolving these pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 54 publications
4
72
0
Order By: Relevance
“…For instance, ACC has been shown to serve as a transient form designed to spontaneously evolve into a preset specific crystalline form with sculptured morphology (9)(10)(11). It has also been shown that ACC can be stabilized to remain in a highly soluble amorphous state, in which case the calcium can be readily retrieved, thus establishing its bioavailability (12,13). These properties of ACC attract extensive scientific, technological, and biomedical interest.…”
mentioning
confidence: 99%
“…For instance, ACC has been shown to serve as a transient form designed to spontaneously evolve into a preset specific crystalline form with sculptured morphology (9)(10)(11). It has also been shown that ACC can be stabilized to remain in a highly soluble amorphous state, in which case the calcium can be readily retrieved, thus establishing its bioavailability (12,13). These properties of ACC attract extensive scientific, technological, and biomedical interest.…”
mentioning
confidence: 99%
“…CaCO 3 is known to occur in unstable and more stable polymorphs. The CaCO 3 polymorphs in decreasing stability are: calcite, aragonite, vaterite, monohydrocalcite, ikaite and amorphous calcium carbonate (Meiron et al, 2011;Radha et al, 2010). Although CaCO 3 deposition in anaerobic reactors is commonly occurring and therefore it has been extensively studied (Langerak et al, 1999;Lier & Boncz, 2002), its interconnections with silicate mineral dissolution and biogas improvement have not been studied.…”
Section: Theoretical Aspectsmentioning
confidence: 99%
“…Five of these are crystalline and one is amorphous (hydrated amorphous calcium carbonate (Meiron et al, 2011). Of the five crystalline forms, three are anhydrous crystalline (i.e., calcite, aragonite, and vaterite) and two are hydrated crystalline (i.e., crystalline monohydrocalcite and ikaite) (Meiron et al, 2011). The most thermodynamically stable of these forms is calcite, whereas the least stable is the amorphous form (Nebel et al, 2008;Meiron et al, 2011).…”
Section: Terms Of Reference As Provided By the European Commissionmentioning
confidence: 99%
“…Particles of amorphous calcium carbonate are reported to be characteristically 40 to 120 nm diameter spherules, in contrast to the 1 to 10 µm diameter crystals typical of the other forms (Meiron et al, 2011). According to the Calcium Carbonate Association (CCA-Europe) engineered nanoscale calcium carbonate is not used as a food additive.…”
Section: Terms Of Reference As Provided By the European Commissionmentioning
confidence: 99%
See 1 more Smart Citation